Central Asia, Euro-centrism and Colonialism - N. T. Nurulla-Khodzhaeva (MGIMO University Press, 2015)
The following article should not be dismissed as yet another attempt to construct a renewed round ofrevisionism in history. On the contrary, it aims to explore the possibility of scaling down the dominant Eurocentric epistemology that served as a basis for a stereotypical frame of knowledge about Central Asia. The majority of researchers of the region do not deem the need to review the scale of contradictory clashes created by the notion of Eurocentrism. The latter is reflected in numerous articles about the frozen (and sadly deadlock) dilemma on why and how were the lands of Tajiks, Uzbeks and Kazakhs divided. By publishing conventional analyses on the region's "clumsy separation", experts illustrate their subaltern, narrowly framed by the colonial world, knowledge and hence, remain as gravestones of the Eurocentric methodology. In the process of such explication, the most important role is allocated to the modern culture, which encouraged the formation of the paradox, represented to us via the paraphrased Soviet aphorism: modernity and coloniality are twin brothers. The initiation of the process of decolonizing the mind within the five republics of the region is possible. One of the solutions involves recognizing the integrity of the pluralist-cycled culture and philosophy of the region. The proposed act will allow shrinking the focus on the knowledge within the limited national units and frames (thus, lessening the degree of'fetishism of the national identity'), and rather creating conditions for designing the "bridge", linking different cultures, ideologies and institutional spaces in Central Asia, as a transnational intellectual matrix. The aforementioned theory will provide a basis and structure for empirical facts, and, therefore, drive the researchers from merely constituting to critically thinking, and consequently, inspire to come upon new approaches and fields of study, connecting them with the existing, colonial experiences. It is essential to highlight that based on this, a new dialogue may commence, where Central Asian scholars are regarded as equals to those of other research schools (both within and outside the region).